Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.3390/md9081346
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Marine Brown Algae and Sponges from Brazil as Anticoagulant and Antiplatelet Products

Abstract: The ischemic disorders, in which platelet aggregation and blood coagulation are involved, represent a major cause of disability and death worldwide. The antithrombotic therapy has unsatisfactory performance and may produce side effects. So, there is a need to seek molecules with antithrombotic properties. Marine organisms produce substances with different well defined ecological functions. Moreover, some of these molecules also exhibit pharmacological properties such as antiviral, anticancer, antiophidic and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 42 publications
0
8
0
1
Order By: Relevance
“…Some studies described marine products from seaweeds as feasible anticoagulants to be explored such as those isolated from the brown alga, Canistrocarpus cervicornis (e.g., heterofucans) [9] and fruits of Ilex paraguariensis [10]. Diterpenes also represent a class of secondary metabolites with high biotechnological potential [11]. Recently, De Andrade Moura and coworkers reported the inhibitory effects against human platelet aggregation and blood coagulation of dichotomanol, a rare exclusively marine diterpene with two aldehyde groups and pachydictyol A and isopachydictyol A which are mainly prenylated derivatives of known guaiane sesquiterpenes, all isolated from the Brazilian marine brown alga Dictyota menstrualis [2] (Figure 2).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Some studies described marine products from seaweeds as feasible anticoagulants to be explored such as those isolated from the brown alga, Canistrocarpus cervicornis (e.g., heterofucans) [9] and fruits of Ilex paraguariensis [10]. Diterpenes also represent a class of secondary metabolites with high biotechnological potential [11]. Recently, De Andrade Moura and coworkers reported the inhibitory effects against human platelet aggregation and blood coagulation of dichotomanol, a rare exclusively marine diterpene with two aldehyde groups and pachydictyol A and isopachydictyol A which are mainly prenylated derivatives of known guaiane sesquiterpenes, all isolated from the Brazilian marine brown alga Dictyota menstrualis [2] (Figure 2).…”
Section: Figurementioning
confidence: 99%
“…Lately, the biotechnological development in the field of marine products have explored potential applications on thrombotic related pathological diseases [2,11,20,21]. In 2014 De Andrade Moura and co-workers described three diterpenes from Dictyota menstrualis (pachydictyol A, isopachydictyol A and dichotomanol) as inhibitors with direct effect on Thrombin catalytic activity against its natural (fibrinogen) and synthetic (chromogenic-S2238) substrates [2].…”
Section: Introductionmentioning
confidence: 99%
“…Como nas algas verdes, há vários artigos de atividades biológicas de extratos de algas pardas. [56][57][58] Sem dúvida, os produtos naturais de algas pardas marinhas têm um grande potencial para diversas atividades biológicas, sendo o grupo de macroalga mais estudado no Brasil em relação à química de produtos naturais. …”
Section: Produtos Naturais De Algas Pardas Marinhasunclassified
“…The seas provide an amazing source of molecules when compared to the terrestrial environment; however, little is known about their biological or pharmacological functions. Marine organisms produce molecules derived from primary and secondary metabolism with biological and pharmacological effects, such as antiviral, anticancer, anticoagulant and antiplatelet activities [ 22 - 26 ]. Previously, antivenom activity has been described in marine algae and sponges, which showed that both organisms can inhibit some toxic effects of Lachesis muta and B. jararaca venoms [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%